1993
DOI: 10.1002/1097-0142(19931001)72:7<2186::aid-cncr2820720720>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of malignancies in renal transplant recipients

Abstract: Background. The incidence of cancers after renal transplantation is significantly higher than in populations that have not undergone transplantation. The authors report a group of renal transplant patients from the University of Cincinnati who had cancer develop; the focus is on the patients' clinical course. Methods. Since 1968, 876 renal transplantations have been performed for a variety of causes of end stage renal disease. Charts of transplant patients who had neoplasms were reviewed. Results. Forty‐four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(86 citation statements)
references
References 4 publications
3
79
1
3
Order By: Relevance
“…A tendency toward aggressive behavior has been noted in malignancies in renal transplant recipients. 87 Although instances of tumor regression with cessation or reduction in the immunosuppressant regimen have been noted in PTLD, 47 most nonlymphoid de novo nonskin cancers follow a virulent course unchecked by return to normal immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…A tendency toward aggressive behavior has been noted in malignancies in renal transplant recipients. 87 Although instances of tumor regression with cessation or reduction in the immunosuppressant regimen have been noted in PTLD, 47 most nonlymphoid de novo nonskin cancers follow a virulent course unchecked by return to normal immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…The management for the prevention of organ rejection requires the use of immunosuppressive therapy during the postoperative periods. However, it is a serious problem that immunosuppressants increase the incidence of skin cancer and sarcoma and induce cancer progression causing incremental fatality of transplant recipients (1-3), because malignant tumors in transplant recipients are frequently more aggressive than similar malignancy in the general population (4). In the field of liver transplantation, it has been accepted that liver transplantation is an effective treatment for small, unresectable hepatocellular carcinoma (HCC) 3 in patients with cirrhosis (5) and it was recently reported that a significant proportion of patients with HCC measuring 5 cm or larger can achieve long-term survival after liver transplantation in the context of multimodal adjuvant therapy (6).…”
Section: Il-12 Gene Therapy Is An Effective Therapeutic Strategy Formentioning
confidence: 99%
“…[4][5][6] AML following solid organ transplantation is less frequent. 7,8 Several cases with AML post-renal transplantation have been published. 7,[9][10][11][12][13][14][15][16][17][18][19] One patient with AML out of a series of 124 cardiac allograft recipients has been reported.…”
Section: Introductionmentioning
confidence: 99%